Kebebasan dan Tanggung Jawab dalam Bumi Manusia - M. Samsul Ma'arif; Diah Dwi Ikranegara (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: Freedom and Responsibility in Human Earth. Human Earth is a very popular read and has been translated into various foreign languages. However, Earth of Mankind was once banned from publication, because it was considered to contain propaganda for Communist teachings, Marxism-Leninism. This teaching is dangerous because it contradicts the Pancasila ideology This study aims to reveal how the messages in Earth of Mankind relate to freedom and responsibility. This research uses an objective hermeneutic method as an interpretative approach so that this study can objectively reveal the messages of Human Earth. The results of the study reveal that the Human Earth message adds insight into life in reality. Freedom and responsibility must be owned by both parties and the two must work in balance. Like a